(untitled) (Trabalho & Educação, 2017)
This article refers to studies about suffering at work and, in this bias, it explores stress in the socioconomic context, and professional development. The article demonstrates that workers’ concerns about stress increased from 22% in 2005 to 25% in 2010. It is also reported that stress leave is higher in the less hazardous sectors and that in small businesses, stress is not commented and still affirms that the fragility of the collective contributes to the increase of this stress. Another factor that contributes to the suffering at work, verified in the study, is the proximity of the management. The dramatic rise in the stress complaint since the end of the 1990s has multiple causes and explanations (intensification of work, development of the service sector, the hegemony of the psychological culture, etc.). Among these evolutions, the decline of the workers’ collectives and the occupations’ culture on which they were leaned explains a lesser collective resistance and resilience to difficulties met at work. In the absence of social representations shared by the work group and communal definition of what a “good job” is, it’s more difficult to give meaning to the realized activities, to feel the recognition for the supplied efforts. The employees then suffer more when facing the daily problems, they no longer help each other neither share “tricks” to overcome difficulties, to manage conflicts and dysfunctions. Work is no longer evaluated by people who know the job, but in an abstract way abstracted by administrators or accountant who do not know the business. Results are contradictory orders, unrealistic objectives, feeling not to be rightly recognized. All these evolutions leave workers alone facing their own suffering and expressing it more often in the psychological register of stress. ___ Este artigo refere-se aos estudos sobre o sofrimento no trabalho e, nesse viés, ele explora o estresse no contexto social, econômico e profissional. O artigo demonstra que a preocupação dos trabalhadores, com relação ao estresse, aumentou de 22% em 2005 para 25% em 2010. Também é relatado que as licenças por estresse são maiores nos setores menos perigosos e que, nas pequenas empresas, o estresse não é comentado e ainda afirma que a fragilidade dos coletivos contribui para o aumento desse estresse. Outro fator que contribui para o sofrimento no trabalho, verificado no estudo, é a proximidade da gerência. O forte crescimento da queixa de estresse desde o final da década de 1990 tem muitas causas e origens (intensificação do trabalho, terciarização da economia, hegemonia do discurso psicológico etc.). Entre essas evoluções, o enfraquecimento dos coletivos de trabalho e das profissões em que foram apoiadas explica uma menor resistência e resiliência coletiva às dificuldades encontradas no trabalho. Na ausência de representações compartilhadas do trabalho e do “belo trabalho”, é mais difícil dar sentido às atividades realizadas, encontrar o reconhecimento dos esforços desenvolvidos. Os funcionários acham mais difícil lidar com os problemas do dia a dia, para ajudar uns aos outros e para compartilhar “truques” para superar dificuldades, gerenciar conflitos e disfunções. O trabalho não é mais avaliado por pessoas do ofício, mas, de maneira abstrata, por gerentes que não estão familiarizados com as atividades. Daí as injunções contraditórias, os objetivos irrealistas, o sentimento de não ser reconhecido pelo seu verdadeiro valor. Todas essas evoluções levam a deixar o trabalhador sozinho para enfrentar seu sofrimento e expressá-lo com mais frequência sob o registro psicológico do estresse